Hybridation et dispositifs hybrides de formation dans l'enseignement supérieur : revue de la littérature 2012-2020 - Claire Peltier; Catherine Séguin (Centre National d'Enseignement à Distance, 2021)
Blended learning has of interest to researchers, teachers, practitioners and institutional decision makers for several decades. The work carried out by a group of French-speaking researchers (Hy-Sup, 2009-2012) has contributed to a better understanding of what these learning environments are, their diversity, and their effects on the various actors involved in their implementation and experimentation. Often used in the French-speaking educational world, this work seems to be little known by English-speaking researchers. The aim of this study is to take stock, almost ten years after the end of the Hy-Sup project, of the terminology, definitions and research relating to hybrid training systems, through the analysis of a selection of texts published on the subject between 2012 and 2020 in French and English.